Potential mechanisms underlying the association between feeding and eating disorders and autism - Adams, K; Mandy, W; Catmur, C; Bird, G (Elsevier, 2024)
There is a reliable association between autism and Feeding and Eating Disorders. Concerningly, where these two conditions co-occur, clinical outcomes of Feeding and Eating Disorders are significantly worse, and treatment less effective, than when the Feeding and Eating Disorders occur in neurotypical individuals. Problematically, the reason for the association between autism and Feeding and Eating Disorders is poorly understood, which constrains advances in clinical care. This paper outlines several possible mechanisms that may underlie the observed association and suggests ways in which they may be empirically tested. Mechanisms are split into those producing an artefactual association, and those reflecting a genuine link between conditions. Artefactual associations may be due to conceptual overlap in both diagnostic criteria and measurement, Feeding and Eating Disorders causing transient autistic traits, or the association being non-specific in nature. A genuine association between autism and Feeding and Eating Disorders may be due to common causal factors, autism directly or indirectly causing Feeding and Eating Disorders, and Feeding and Eating Disorders being a female manifestation of autism.